2010
DOI: 10.2193/2007-506
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Predator Harvest, Biological Factors, and Landscape on Elk Calf Survival in Idaho

Abstract: We evaluated survival of elk (Cervus elaphus) calves on 2 contrasting study areas in north‐central Idaho, USA, from 1997 to 2004. Recruitment was modest (>30 calves:100 F [calves of either sex: F elk 1 yr old]) and stable on the South Fork study area and low (<20 calves:100 F) and declining on the Lochsa study area. The primary proximate cause of calf mortality on both study areas was predation by black bears (Ursus americanus) and mountain lions (Puma concolor). We experimentally manipulated populations of bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
100
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(124 citation statements)
references
References 37 publications
(58 reference statements)
17
100
3
Order By: Relevance
“…In contrast, we detected a strong relationship between calf recruitment and the number of bears relocated annually, which would be unaffected by such biases. Our findings are consistent with other manipulative studies on elk calf predation by black bears in the western United States (Schlegel 1986, White et al 2010), though our study lacked randomization and a control necessary to demonstrate a strict causal relationship.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In contrast, we detected a strong relationship between calf recruitment and the number of bears relocated annually, which would be unaffected by such biases. Our findings are consistent with other manipulative studies on elk calf predation by black bears in the western United States (Schlegel 1986, White et al 2010), though our study lacked randomization and a control necessary to demonstrate a strict causal relationship.…”
Section: Discussionsupporting
confidence: 91%
“…Raithel et al (2007) used life‐stage simulation analysis to show that annual variation in calf survival may be the dominant influence on short‐term variation in elk population growth. Bears are efficient predators of neonatal ungulates, particularly when hiding cover is limited (Gunther and Renkin 1990, Mattson 1997, Vreeland et al 2004, Onorato et al 2006, White et al 2010). The elk releases and most known birth sites (24 of 32 births) from 2001 to 2005 occurred in Cataloochee Valley, North Carolina, USA, in the southeastern section of GSMNP (Murrow 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have also found evidence that black bears may negatively affect recruitment of calves in a reintroduced population of elk in the eastern U.S. (Yarkovich et al 2011), but research has also suggested that predation appears to have a larger affect at lower ungulate densities (Zagar and Beechum 2006). In Idaho, elk calf survival seemed to be influenced by birth weight, habitat structure, and black bear and cougar harvest (presumably in relation to their respective densities); calf mortality through predation by black bears was described as additive (i.e., in addition to, rather than replacing, other sources), and the authors suggested that a spring bear season may be effective for improving calf survival (White et al 2010). The actual significance of predation of ungulates by black bears is likely dependent on a complex relationship involving bear densities, ungulate densities, presence and densities of other predators, weather conditions, and alternate food availability (e.g., Beechum 2006, Griffin et al 2011).…”
Section: Foraging and Predationmentioning
confidence: 99%
“…Neonatal mortality in ungulates is sensitive to variation in numerous biological and environmental factors [6], but especially body condition at birth [2], [3], [7], limiting resources (e.g., hiding vegetation; [8], [9]), and predation [10]. These factors are often interrelated and affect survival directly through predation or indirectly through resource use and maternal nutritional effects, which can influence neonate body growth and consequently survival [11], [12], [13].…”
Section: Introductionmentioning
confidence: 99%